2011
DOI: 10.1117/12.892530
|View full text |Cite
|
Sign up to set email alerts
|

Driving experience and special skills reflected in eye movements

Abstract: When driving a vehicle, people use the central vision both to plan ahead and monitor their performance feedback (research by Donges, 1978 [1], and after). Discussion is ongoing if making eye movements do more than gathering information. Moving eyes may also prepare the following body movements like steering.Different paradigms exist to explore vision in driving. Our perspective was to quantify eye movements and fixation patterns of different proficiency individuals, a driving learner, a novice, an experienced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Increased cognitive workload in a complex traffic environment causes the useful field of view to narrow, thus, decreasing the fixation duration [8]. Several previous studies have found differences in eye movements according to driving experience and/or traffic conditions, such as the type of road or the amount of traffic information [7][8] [9].…”
Section: Introductionmentioning
confidence: 99%
“…Increased cognitive workload in a complex traffic environment causes the useful field of view to narrow, thus, decreasing the fixation duration [8]. Several previous studies have found differences in eye movements according to driving experience and/or traffic conditions, such as the type of road or the amount of traffic information [7][8] [9].…”
Section: Introductionmentioning
confidence: 99%
“…The first is that high fixation density areas cannot be predicted before eye-movement data are acquired. For example, when participants are asked to drive in rural areas [44] or city roads [64] for a long time, it is difficult to predict the high fixation density area in advance. The second is that there are similar studies to refer to for appropriate and quick AOI definition.…”
Section: A Expert Defined Aoismentioning
confidence: 99%
“…In contrast, there are many studies about experience and expertise issue using eye trackers regarding in automobile and aviation areas. Konstantopoulos et al [ 23 ] and Paeglis et al [ 13 ] studied the experience and expertise of drivers considering mainly on fixation related data such as mean fixation duration, mean fixation number, total fixation percentage on AOIs (area of interest), fixation percentage on specific AOIs. In this topic, scanpath comparison method is also utilized to distinguish between novice and expert.…”
Section: Related Workmentioning
confidence: 99%
“…Eye tracking is implemented in many research areas with respect to training. For example, Kasarskis et al [ 3 ], Sadasivan et al [ 4 ], Sarter et al [ 5 ], Yang et al [ 6 ], Kang & Landry [ 7 ], Dehais et al [ 8 ] and Wickens et al [ 9 ] implemented eye tracking techniques to study flight training with a focus on fixation number, mean fixation duration, mean dwell duration and scanpath; Balk et al [ 10 ], Fisher et al [ 11 ], Palinko et al [ 12 ], Paeglis et al [ 13 ], and Xu et al [ 14 ] studied driving training by analyzing mean fixation duration and its standard deviation, saccade size, pupil diameter and scanpath; Miall & Tchalenko [ 15 ], and Tchalenko [ 16 ] researched drawing issues introducing dwell time; Law et al [ 17 ], and Chetwood et al [ 18 ] carried out surgery training; Kovácsová et al [ 19 ] researched cyclists’ eye movements by introducing fixation duration; Although many successes of eye tracking applications validate the feasibility in human training, it is seldom to see applying eye tracking technology to marine operation training [ 20 ], much less researches on analyzing and evaluating eye behavior during the training.…”
Section: Introductionmentioning
confidence: 99%